2010
DOI: 10.1097/shk.0b013e3181cd86d6
|View full text |Cite
|
Sign up to set email alerts
|

ACTIVATION OF PEROXISOME PROLIFERATOR-ACTIVATED RECEPTOR-β/δ ATTENUATES MYOCARDIAL ISCHEMIA/REPERFUSION INJURY IN THE RAT

Abstract: Peroxisome proliferator-activated receptor-beta/delta (PPAR-beta/delta) is a transcription factor that belongs to the PPAR nuclear hormone receptor family. There is little information about the effects of the immediate administration of specific ligands of PPAR-beta/delta (e.g., GW0742) in animal models of myocardial I/R injury. Using a rat model of regional myocardial I/R in vivo, we have investigated the effects of immediate administration of GW0742 on myocardial infarct size. Male Wistar rats were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 33 publications
1
48
0
2
Order By: Relevance
“…The present results, showing an attenuation of SCIinduced up-regulation of TNF-␣ and iNOS by GW0742 are in good agreement with these previous reports showing antiinflammatory effects of PPAR-␤/␦ agonist. These effects could be mediated through regulation of the NF-B pathway, as it had been proposed previously (Kapoor et al, 2009).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The present results, showing an attenuation of SCIinduced up-regulation of TNF-␣ and iNOS by GW0742 are in good agreement with these previous reports showing antiinflammatory effects of PPAR-␤/␦ agonist. These effects could be mediated through regulation of the NF-B pathway, as it had been proposed previously (Kapoor et al, 2009).…”
Section: Discussionmentioning
confidence: 79%
“…The dose of GW0742 (0.3 mg kg Ϫ1 ) used here was based on a previous dose-response study in a myocardial ischemia and reperfusion study (Kapoor et al, 2009). GW0742 has an EC 50 value of 1 nM compared with 1 and 2 mM for PPAR-␣ and PPAR-␥, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The peroxisome proliferator-activated receptors (PPARa, b, and c) (8,18,26), liver X receptors (22,29), thyroid hormone receptor (46), estrogen receptors (30), androgen receptors (57), and glucocorticoid receptor (25) have been proposed as the endogenous cardioprotective receptors against MI/R injury, while farnesoid-X-receptor (52), mineralocorticoid receptors (32,54), and Nur77 (12) exacerbate MI/R-induced myocardial injury. Our study adds novel evidence that VDR acts as an endogenous cardioprotective nuclear receptor against MI/R injury.…”
Section: Vdr Attenuates Mi/r Injurymentioning
confidence: 99%
“…Leukocyte infiltration and the related release of proinflammatory cytokines are known to significantly contribute to the tissue injury evoked by reperfusion of ischemic organs and events of organ-related ischemia/reperfusion (I/R) injury, such as myocardial and cerebral infarction, are among the most critical cardiovascular complications evoked by metabolic disorders. We and others have demonstrated that ligand activation of PPAR / evoke organ protection in experimental models of myocardial, renal, intestinal and lung I/R injury by disrupting multiple levels of the inflammatory cascade [88][89][90][91][92]. Similarly, selective PPAR / genetic deletion has been demonstrated to result in both increased kidney dysfunction and brain infarction in mice [91,93].…”
Section: Ppar / Activation and Cardiovascular Complications Of The Metsmentioning
confidence: 89%